OÐ¿Ñ€ÐµÐ´ÐµÐ»ÐµÐ½Ð¸Ðµ Ð¼Ð¾Ð´ÑƒÐ»Ñ ÑÐ´Ð²Ð¸Ð³Ð° Ð¼ÐµÐ¼Ð±Ñ€Ð°Ð½ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð², Ð½Ð°Ñ…Ð¾Ð´ÑÑ‰Ð¸Ñ…ÑÑ Ð² ÑÑƒÑÐ¿ÐµÐ½Ð·Ð¸Ð¸ - Gordienko, E. A.; Todrin, A. F.; Osetsky, A. I.; Popivnenko, L. I. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2010)
A dynamic method and a device are described; an algorithm for calculation of the average shear modulus of membranes of suspended erythrocytes flowing through a flat canal is suggested. Experimental data on erythrocyte membrane shear modulus depending on temperature and terms of hypothermic storage of blood are presented.